The diversity of lepidopteran spatial orientation strategies – neuronal mechanisms and emerging challenges in a changing world - Robin Grob; Max S. Farnworth; Jacqueline Degen; Eric Warrant; Stephen H. Montgomery; Basil el Jundi (Journal of Comparative Physiology A, 2026)
The Lepidoptera, butterflies and moths, display an astonishing diversity of spatial orientation strategies essential for survival, reproduction, and ecological success. These spatial orientation strategies range from basic taxes to light, wind, gravity, and chemical cues, to more advanced strategies such as straight-line dispersal, multigenerational migration across continents, and complex trap-lining foraging involving long-term spatial memory. These orientation behaviours are tightly integrated with the ecological roles of lepidopterans as pollinators, prey, and bioindicators, and are supported by a flexible neuronal network. Of special interest for successful orientation are higher-order integration centres like the mushroom bodies (centres for learning and memory) and the central complex (the centre for spatial orientation and locomotion). These centres support cue integration, compass orientation, memory, and directional decision-making. However, anthropogenic stressors, including habitat fragmentation, light pollution, pesticides, and electromagnetic noise, threaten both the environmental cues and the neural systems facilitating lepidopteran navigation, with potential cascading effects on biodiversity and ecosystem health. By combining insights from behavioural ecology, neurobiology, and conservation, we aim to provide a comprehensive overview of the challenges and adaptations that shape the navigational toolkit of lepidopterans, underlining their significance as animal models for studying spatial orientation in a changing world.